2014
DOI: 10.1152/ajpendo.00641.2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term niacin treatment induces insulin resistance and adrenergic responsiveness in adipocytes by adaptive downregulation of phosphodiesterase 3B

Abstract: Heemskerk MM, van den Berg SA, Pronk AC, van Klinken JB, Boon MR, Havekes LM, Rensen PC, Willems van Dijk K, van Harmelen V. Long-term niacin treatment induces insulin resistance and adrenergic responsiveness in adipocytes by adaptive downregulation of phosphodiesterase 3B. Am J Physiol Endocrinol Metab 306: E808 -E813, 2014. First published January 28, 2014; doi:10.1152/ajpendo.00641.2013.-The lipid-lowering effect of niacin has been attributed to the inhibition of cAMP production in adipocytes, thereby inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 27 publications
3
31
2
2
Order By: Relevance
“…As previously published ( 16 ), niacin treatment did not lead to differences in body weight nor gWAT weight in these mice. However, plasma lipids (i.e., total cholesterol, TGs, and phospholipids) were all decreased ( 16 ).…”
Section: Gwat Gene Expression Analysissupporting
confidence: 84%
See 3 more Smart Citations
“…As previously published ( 16 ), niacin treatment did not lead to differences in body weight nor gWAT weight in these mice. However, plasma lipids (i.e., total cholesterol, TGs, and phospholipids) were all decreased ( 16 ).…”
Section: Gwat Gene Expression Analysissupporting
confidence: 84%
“…As previously published ( 16 ), niacin treatment did not lead to differences in body weight nor gWAT weight in these mice. However, plasma lipids (i.e., total cholesterol, TGs, and phospholipids) were all decreased ( 16 ). Gene expression analysis generated 24 differentially expressed genes due to niacin treatment after multiple test correction (adjusted P < 0.05, see Table 1 ).…”
Section: Gwat Gene Expression Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…has also been reported to occur in mice ( 41 ). In the lean (Sprague Dawley) rats used in the current study, we observed no signifi cant change in PDE-3B mRNA after 5 days of continuous NiAc infusion.…”
Section: Discussionsupporting
confidence: 60%